Correlation between the Antibiotic Resistance Genes and Susceptibility to Antibiotics among the Carbapenem-Resistant Gram-Negative Pathogens - Salma M. Abdelaziz; Khaled M. Aboshanab; Ibrahim S. Yahia; Mahmoud A. Yassien; Nadia A. Hassouna (MDPI AG, 2021)
In this study, the correlation between the antibiotic resistance genes and antibiotic susceptibility among the carbapenem-resistant Gram-negative pathogens (CRGNPs) recovered from patients diagnosed with acute pneumonia in Egypt was found. A total of 194 isolates including Klebsiella pneumoniae (89; 46%), Escherichia coli (47; 24%) and Pseudomonas aeruginosa (58; 30%) were recovered. Of these, 34 (18%) isolates were multiple drug resistant (MDR) and carbapenem resistant. For the K. pneumoniae MDR isolates (n = 22), blaNDM (14; 64%) was the most prevalent carbapenemase, followed by blaOXA-48 (11; 50%) and blaVIM (4; 18%). A significant association (p value < 0.05) was observed between the multidrug efflux pump (AcrA) and resistance to β-lactams and the aminoglycoside acetyl transferase gene (aac-6'-Ib) gene and resistance to ciprofloxacin, azithromycin and β-lactams (except for aztreonam). For P. aeruginosa, a significant association was noticed between the presence of the blaSHV gene and the multidrug efflux pump (MexA) and resistance to fluoroquinolones, amikacin, tobramycin, co-trimoxazole and β-lactams and between the aac-6'-Ib gene and resistance to aminoglycosides. All P. aeruginosa isolates (100%) harbored the MexAB-OprM multidrug efflux pump while 86% of the K. pneumoniae isolates harbored the AcrAB-TolC pump. Our results are of great medical importance for the guidance of healthcare practitioners for effective antibiotic prescription.